Mind over matter: perceived phantom/prosthesis co-location contributes to prosthesis embodiment in lower limb amputees - Bekrater-Bodmann, Robin (Consciousness and cognition, 2022)
Prosthesis embodiment - the cognitive integration of a prosthesis into an amputees’ body representation - has been identified as important for prosthetic rehabilitation. However, the underlying cognitive mechanisms remain unclear. There is reason to assume that phantom limbs that are experienced as part of the bodily self (phantom self-consciousness) can affect prosthesis embodiment, but only if the phantom and the prosthesis can be brought into perceived co-location (phantom prosthesis tolerance, PPT). In the present study, phantom-prosthesis interactions were examined in lower limb amputees, and a PPT component was psychometrically extracted. Mediation analysis revealed an indirect-only effect, where the relationship between phantom self-consciousness and prosthesis embodiment was mediated by PPT, indicating that phantom limbs can transfer their immanent vividness to the prosthesis. Subsequent analyses suggested that this effect can compensate for negative consequences on prosthesis embodiment that arise from phantom limb awareness. These results shape theoretical considerations about the cognitive processes contributing to the bodily self.
Gesehen am 30.06.2022